KOMBINASI WALKING EXERCISE DAN HYDROTHERAPY MEMPENGARUHI KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE II - Siti Robiatus Sholiha; Sudiarto Sudiarto; Syamsul Arif Setyonegoro (JENDELA NURSING JOURNAL, 2019)
Background: The blood glucose levels in patients Type II diabetes mellitus If are not controlled it will worse condition. One attempt to reduce blood glucose levels is by walking exercise and hydrotherapy.Purpose: To understand the influence of a combination of walking exercise and hydrotherapy to decrease blood glucose levels in patients with type II diabetes mellitus.Methods: This research method is Quasy Experiment with the pre and post test with control group design. The number of samples are 48 people were divided into 2 groups that is intervention combination of walking exercise and hydrotherapy and control groups. The sampling technique was simple random sampling. The data analysis uses Dependent t-test and Independent t-test.Results: The results dependent t-test showed that there were a significant difference in the pre and post of blood sugar levels of the intervention group with p value 0,000 ( 0,05) and the control group with p value 0,008 ( 0,05). Independent t-test obtained results p value 0.000 (≤ 0.05) showed that there is the influence of a combination of walking exercise and hydrotherapy to blood glucose levels.Conclusion: In this study showed that there is the influence of a combination of walking exercise and hydrotherapy to blood glucose levels in patients type II diabetes mellitus.